Carrier mobility dynamics under actual working conditions of organic solar cells - Jasiūnas, Rokas; Jašinskas, Vidmantas; Zhang, Huotian; Upreti, Tanvi; Gao, Feng; Kemerink, Martijn; Gulbinas, Vidmantas (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
Although organic photovoltaics has made significant progress since its appearance decades ago, the underlying physics of charge transport in working cells is still under debate. Carrier mobility, determining the carrier extraction and recombination, is one of the most important but complex and still poorly understood parameters. Low-energy charge carrier states acting as traps play a particularly important role in carrier transport. Occupation of these states under real operation conditions of solar cells induces additional complexity. In this study, we use several transient methods and numerical modeling to address carrier transport under actual working conditions of bulk heterojunction organic solar cells based on fullerene and nonfullerene acceptors. We show that occupation of low-energy states strongly depends on the blend materials and the effective electric field. We define conditions when such occupation increases carrier mobility, making it less time-dependent on the microsecond time scale, and when its influence is only marginal. We also show that the initial mobility, determined by carrier relaxation within the high-energy part of the distributed density of states, strongly decreases with time independently of the low-energy state population.